Photocatalytic activity of Ag-doped TiO2 with anatase structure under UV light and simulated sunlight - ZHU Xiao-dong (Journal of Materials Engineering, 2019)
Ag-TiO2 photocatalysts with different doping concentration were prepared by sol-gel method using tetrabutyl titanate and silver nitrate as raw materials. The crystal structure, surface morphology, chemical composition, optical properties of the samples were characterized by XRD, SEM, XPS, DRS and PL, respectively. The photocatalytic activity of xAg-TiO2(x=1%,2%,4%,6%,atom fraction) under UV light and simulated sunlight was evaluated by the degradation of Rhodamine B by using mercury lamp and xenon lamp as the light source, respectively. The results indicate that the photocatalytic activity of TiO2 under UV light and simulated sunlight enhances as the recombination rate of photogenerated electron-hole decreases and the absorption of simulated sunlight increases by Ag doping. 1%Ag-TiO2 exhibits the best photocatalytic activity. The degradation rates of Rhodamine B are 91% under UV light and 89% under simulated sunlight, which are 1.18 and 1.24 times higher than that of pure TiO2. The reaction rate constants are 0.01257 min-1 and 0.01150 min-1, which are 1.49 and 1.74 times higher than that of pure TiO2.